ANALISIS KUALITAS LAYANAN FUNGSI SUMBER DAYA MANUSIA SEBAGAI MITRA BISNIS MENURUT PERSEPSI KARYAWAN DI PT X - Christine Winstinindah Sandroto (Center for Economic Studies Universitas Katolik Parahyangan, 2012)
The purpose of this research is finding how is the HR function’s service quality as a business partner in PT X according to employee perception. Employees are one of the stakeholders and internal customer of HR function. There are four roles for HR to be a business partner; they are strategic partner, change agent, administrative expert, and employee champion. This research shows that HR role’s performance is good in administrative expert, but for three others roles are moderate. Beside that, employee’s expectation for all roles is in good scale. We find that service quality, which is the gap between performance and expectation’s result are: HR service quality in the role of strategic partner, administrative expert, and employee champion is very satisfied, but in change agent is satisfied. Based on further analysis, we found that there is none in HR function service quality which is first priority to be improved in its four roles. Many factors are good and should be maintained the service quality for each role. There are some factors which include in second priority to be improved in each role. For next research, HR function service quality analysis should be seen not only from employees’ perspective, but also from other stakeholder point of view.Key words: service quality, HR function, business partner